Magnetic Properties of Fe and Ni Doped SnO2 Nanoparticles - Ravi Kumar; K.D.Verma; Shalendra Kumar; Mayora Varshney; Aditya Sharma (Nanomaterials and Nanotechnology)
In this work, we report the room temperature ferromagnetism in Sn1‐xFexO2 and Sn1‐xNixO2 (x = 0.00, 0.03 and 0.05) nano‐crystalline powders. All the samples were prepared using co‐precipitation method. X‐Ray Diffraction (XRD), transmission electron microscopy (TEM), energy dispersive x‐ray analysis (EDAX), UV‐ visible absorption spectroscopy and room temperature magnetization measurements were performed to study the crystal structure, morphology, elemental analysis, optical band gap and magnetic properties of Fe and Ni doped SnO2. TEM results depict the formation of spherically shaped and small sized nanoparticles of the diameter of ~ 3 nm. The band gap energy of the Fe and Ni doped samples found to decrease with increasing their concentrations. The higher saturation magnetization was observed in low concentration Fe and Ni doped tin oxide.